Nuclear Data Sheets for A=191 - Basunia, M.S. (Nuclear data sheets, 2024)
Evaluated spectroscopic data and level schemes from radioactive decay and nuclear reaction studies are presented for 191Hf, 191Ta, 191W, 191Re, 191Os, 191Ir, 191Pt, 191Au, 191Hg, 191Tl, 191Pb, 191Bi, 191Po, and 191At. This evaluation for A=191 supersedes the earlier one by V.R. Vanin et. al. (2007Va21), published in Nuclear Data Sheets 108, 2393 (2007).